Diazo Red B Dye Removal by Electrocoagulation Method using Aluminum Electrode - Emriadi, Emriadi; Refinel, Refinel; Khalishah, Salwa (Graduate School of Universitas Syiah Kuala, 2024)
The removal of diazo red B dye was studied in water using the electrocoagulation method with an aluminum electrode. The study aimed to reduce the presence of harmful diazo red B dyes in the environment and their impact on living organisms. This study was conducted by testing various parameters with specified values. The initial dye concentrations were set at 10, 20, 30, 40, and 50 mg/L, while the electrocoagulation times were varied at 30, 60, 90, 120, 150, and 180 minutes. The initial pH levels were adjusted to 5, 6, 7, and 8. The applied voltages were 2.5, 5, 7.5, 12.5 V, and the distances between electrodes varied at 1, 1.25, 1.5, 1.75, and 2 cm. The study also examined the effects of initial dye concentration on electrocoagulation time, its interaction with pH, and the influence of pH on electrocoagulation time. These parameters aim to determine the optimum conditions for diazo red B removal, as measured by a UV-Vis spectrophotometer at a wavelength of 420 nm. The optimum removal efficiency of diazo red B was achieved with 94.32% for an initial dye concentration of 30 mg/L, 94.13% for an electrocoagulation time of 180 minutes, 96.00% at a pH of 6, 95.32% for a voltage of 7.5 V, and 95,75% for an electrode distance of 1.5 cm. Additionally, the efficiencies were 99.5% for concentration relative to time was 99.5%, for concentration relative to pH was 97.85%, and for pH relative to time was 96.00%. Additionally, the coagulant analysis of the electrocoagulation results was carried out using FTIR and morphological analysis of the surface of the damaged aluminum anode using an optical microscope.